A LETTER RELATED TO THE PAYMENT OF ZAKAT TO THOSE WHO HAVE REACHED THE AGE OF MAJORITY STUDY AND INVESTIGATION - M.D. Falah Abdul Rasoul Hammoudi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Praise be to God, Lord of the worlds, and may blessings and peace be upon our Master Muhammad and upon all his family and companions, and after: Indeed, one of the blessings of God Almighty upon the people of Islam is that he pleased this great Sharia and made, with his success, sincere working scholars to explain to people the matters of their religion and what their uneasy understanding of the Shari’a matters pertaining to them, so the efforts of scholars in this field were great and their benefit was abundant by answering people's questions and the good simplicity of what they were asking about With the clear legal evidence that came out in the texts, and the effort that he made here is related to a written message that Imam Shams al-Din al-Nababi was asked about, and he answered clearly the evidence with the simplification of texts that fulfill the issue its right, so I investigated it according to the scientific method To achieve the texts and its rules, and I made this work in two subjects: The first topic: studying the author's biography and his message on the subject and the method of investigation.